Heat Stress Associated Alterations in Water-Deficit Markersin Sheep from Western Rajasthan - Singhal, Saurabh Singh; Arora, Sunil; Sharma, Vikash Kumar; Abhimnu,; Kataria, A. K.; Kataria, Nalini (International Journal of Bio-resource and Stress Management, 2022)
A study was conductedduring 2018-2019 (Approximately one year) at College of Veterinary and Animal Science, Bikaner, Rajasthanto access the heat ambience associated alterations in water-deficit markers in sheep from western Rajasthan. Appraisal of environmental elements was carried out on the basis of recording of heat load index during intervening, dry-hot, humid-hot and cold Environmental Periods from Sri Ganganagar and Churu districts of Rajasthan. The mean values among EPs varied significantly (p≤0.05) for minimum, maximum and average Temperature Humidity Index (THI). During humid-hot EP, the % variation in the values of plasma bicarbonate, urine bicarbonate,Fractional Excretion of Bicarbonate ions (FEBicarb), plasma anion gap and urine anion gap were found to be maximum (+32.73%, +112.78%, +168.75%, -45.74% and +23.17, respectively. On the basis of study it was concluded that the humid hot was the most effective season among all ambiences. The female sheep were affected more than male sheep. Along with that it was also observed that 15–19 age group was affected the most among all 4 age groups. Among all ambiences, humid hot environmental condition becomes very significant for unorganized farm animals. In study of stress caused by hot environment bicarbonate ions appeared to be the most perceivable analyte representing fluid, electrolyte and acid-base status. It could also be concluded that environmental stress, disturbs the ionic balance so the nutritional and management remedies are required for better health and production of sheep under at unorganised farms.